Antitumor Necrosis Factor-α Therapy Is Associated With Reduced Risk of Thromboembolic Events in Hospitalized Patients With Inflammatory Bowel Disease. Issue 7 (August 2016) - deFonseka, Arushi M.; Tuskey, Anne; Conaway, Mark R.; Behm, Brian W.
Abstract : Background: Patients with inflammatory bowel disease (IBD) are at increased risk of thromboembolic events. The aim of this study was to assess whether treatment with anti-tumor necrosis factor-α (TNF-α) therapy was associated with a decreased risk of thromboembolism. Methods: We identified IBD patients hospitalized between July 2002 and July 2011 at our institution. Demographic data, medications, indication for hospitalization, and type of thromboembolic event were obtained by chart review. Wald tests were used to calculate an association between clinical characteristics and risk of thromboembolism. A multivariable logistic regression model was used to identify independent risk factors for thromboembolic events. Results: A total of 547 patients (1048 hospitalizations) were identified. Fifty thromboembolic events occurred. Patient-related factors associated with thromboembolism included older age ( P <0.0001), chronic kidney disease ( P =0.001), diabetes ( P =0.009), liver disease ( P =0.005), and prior history of thromboembolism ( P <0.0001). Acute infection ( P =0.009), trauma ( P =0.009), prolonged hospitalization ( P <0.0001), and lack of thromboembolic prophylaxis ( P <0.0001) were also associated with increased risk. Systemic corticosteroids were associated with increased risk of thromboembolism ( P =0.003), whereas TNF-α inhibitors were protective ( P =0.011). Multivariate regression identified systemic corticosteroid use (OR=4.62, P =0.0004) as associated with an increased risk of thromboembolism. TNF-α inhibitors were associated with a reduced risk of thromboembolism (OR=0.20, P =0.049). Conclusions: In this cohort of hospitalized IBD patients, TNF-α inhibitor therapy was associated with a reduced risk of thromboembolism, whereas systemic corticosteroid use was associated with an increased risk of thromboembolism.